Analisis Strategi Fundraising Zakat, Infak dan Shodaqah di Lazismu Kabupaten Jepara - Suparwi S; Khofifatur Rohmaniah; Regitta Adeleana Norestanti; Aliyatus Sa’diyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research was conducted at LAZISMU Jepara which is related to the fundraising strategy and distribution of zakat, infaq and shodaqah in order to develop mustahiq small businesses at LAZISMU Jepara.  The aim of this research is to find out existing fundraising strategies at LAZISMU Jepara, to find out the obstacles in implementing fundraising at LAZISMU Jepara, and to get solutions to overcome fundraising obstacles at LAZISMU Jepara.  This research was conducted at LAZISMU Jepara regarding the fundraising strategy for zakat, infaq and shodaqah in order to develop mustahik small businesses at LAZISMU Jepara.  This type of research uses field research with qualitative methods and appropriate depictions in the field.  This research uses primary and secondary data sources to obtain data at LAZISMU Jepara.  Data collection uses observation, interviews, documentation, and analyzing data.  Data analysis by summarizing all the data, and presenting the data.  The results of this research are an analysis of zakat infaq and shodaqah fundraising in efforts to develop mustahik small businesses at LAZISMU Jepara through services provided directly and indirectly which will be distributed to mustahik who are entitled to receive them.  There are also obstacles in carrying out fundraising activities, namely lack of human resources and lack of public awareness.  Meanwhile, the only obstacle that occurs in distribution is the lack of human resources or members.  The solution that can be provided for fundraising activities is by adding human resources and increasing public awareness so that they are willing to channel their zakat and alms funds to LAZISMU Jepara.  Meanwhile, distribution also requires additional high-quality human resources.